(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2015)
Proving an offence is one of the main factors in administering justice in a court of law. This article examines the level of understanding on issues relating to proving criminal cases in Syariah courts such as the evidentiary burden of proof and standard of proof. Misunderstanding of the different terminology and related principles will cause difficulty in making just decisions. This article also looks at the use of admissions made outside the court and testimony given by experts. The writer examines related laws and decisions of the courts. The correct understanding of evidentiary laws is important for prosecutors, lawyers and the courts to make just decisions. Keywords: proving, syariah courts, admission, circumstantial evidence, DNA